CT-guided core needle biopsy of small (≤20 mm) subpleural pulmonary lesions: value of the long transpulmonary needle path. Issue 7 (July 2019) - Yu, J.H.; Li, B.; Yu, X.X.; Du, Y.; Yang, H.F.; Xu, X.X.; Zhang, C.; Li, Y.
Abstract : AIM: To evaluate the accuracy and complications of computed tomography (CT)-guided core needle biopsy (CNB) of small (≤20 mm) subpleural pulmonary lesions with the use of the long transpulmonary needle path. MATERIALS AND METHODS: A retrospective study was undertaken comprising 235 patients who underwent CT-guided CNB of small (≤20 mm) subpleural pulmonary lesions. One of two needle paths was used: a long (≥10 mm) transpulmonary needle path ( n= 164, group A) or a short (<10 mm) transpulmonary needle path ( n= 71, group B). Diagnostic accuracy, pneumothorax, and bleeding rates were compared between the two groups. RESULTS: The diagnostic accuracy in group A was significantly higher than that in group B (93.9% versus 81.7%, p= 0.004), particularly in patients with 5–10 mm lesions (89.2% versus 53.3%, p= 0.013). The mean length of the transpulmonary needle path was 23.9 mm in group A and 5.9 mm in group B ( p< 0.001). The mean number of pleural punctures in group A was 1.01 and 1.11 in group B ( p= 0.016), but for patients with more than one puncture, the short transpulmonary path was not associated with a higher accuracy rate. The incidence of bleeding was 22% in group A and 9.9% in group B ( p= 0.028). CONCLUSION: Diagnostic accuracy for small subpleural pulmonary lesions with the use of the long transpulmonary needle path was higher than that with the use of the short transpulmonary needle path, especially for 5–10 mm lesions; however, the long transpulmonary needle path was associated with a higher rate of bleeding. Highlights: Use of long transpulmonary needle path for biopsy achieved a higher diagnostic accuracy. For patients with more than one puncture, the short transpulmonary route was not associated with a higher accuracy rate. The long transpulmonary needle path resulted in a higher frequency of bleeding.